Distorções e reescritas : o afrofuturismo e a ficção científica distópica em a parábola do semeador, de octavia butler - Silva, Raissa Lauana Antunes da (2022)
When envisioning futures, we see science fiction as a possibility to prospect technological and environmental developments, as well as social and cultural ones. With it, we perceive our present more latently through "what if" narratives, which, by traveling into the future, meet our present. The themes addressed by this genre literature approach the discovery of new worlds, new forms of civilization; but, also, the fear of losing control of one's own destiny, domination by strange bodies, and so many other themes that dialogue directly with black people. Nevertheless, when we historiographically examine this genre literature, we witness a silencing of black narratives that prospect tomorrows or that not only metaphorize themes suffered by minorities, but also bring them from the margins or obscurity to the center. Thinking about these questions, the present work starts from a concern about dystopian science fiction and the presence or absence of black writers in this type of literary production. With this, we arrive at Afrofuturism, which has great prominence in the United States and, little by little, is also beginning to be developed in Brazilian writing. As a critical look that can be applied to science fiction, fantasy and horror, as well as areas focused on art, technology and social activism, Afrofuturism is a movement that questions and demands answers regarding authorship, representation of characters and racial perspectives. In light of this, this dissertation will analyze the dystopia Parable of the Sower by American writer Octavia Butler ([1993] 2018)), which presents a concern with the black view throughout the narrative, distorting and rewriting previously known science fiction patterns. To reach this conclusion, this dissertation will develop in three chapters: the first intends to question the hegemony present in the literature of the real and in science fiction literature. The second will present conceptualizations on Afrofuturism through a sankophilic movement of present, past and future from the glances of Kodwo Eshun (2003), Ytasha Womack (2013), Lisa Yaszek (2019), Lu Ain-Zaila (2019) among other theorists. Finally, the last chapter will analyze the work Parable of the Sower (2018), in order to demystify the non-existence of black science fiction writers, map writing possibilities that escape the hegemonic standard through Afrofuturism and demarcate this movement.